The Correlation Between Adult Age Factors toward The Clinical Manifestation and The Severity Level of COVID-19 in Bengkulu Province in 2020 - Begumratu VOCA; Dia Triyani Putri; Dessy Triana; Riry Ambarsari; Nikki Aldi Massardi; Utari Hartati Suryani (BENCOOLEN JOURNAL OF PHARMACY, 2022)
Coronavirus Disease-19 (COVID-19) is an acute respiratory disease in Wuhan, China, and was discovered discovered in 2019. The things that need to be considered in COVID-19 patients include their clinical manifestation and the severity level of COVID-19. The severity level of COVID-19 patients is associated with age. Each age has a different proportion of severity. The study aimed to determine the correlations among adult age with clinical manifestation and severity of COVID-19 in Bengkulu Province 2020. This study used an observational analytic study. The sample was 108 patients 19 - ≥65 years old and confirmed positive for COVID-19 in 2020. The assessment used the epidemiological investigation form and medical record from Dr. M.Yunus Hospital. At the same time, the severity level of COVID-19 was obtained from the measurement based on the COVID-19 Prevention and Control Guidelines by the Indonesian Ministry of Health. The results showed that the subjects in 19 – 23 years old mostly have asymptomatic severity, 24 – 64 years old mostly have mild severity, and ≥65 years old have moderate severity. It was concluded that there was a significant correlation between the severity of COVID-19 in Bengkulu Province in 2020.